Market demand analysis of affordable housing in Kuching and Samarahan divisions - Donald, Henry Nohed (Universiti Malaysia Sarawak (UNIMAS), 2013)
One of the basic human needs is housing. Therefore, it is pertinent for any country to ensure its‘ citizen have adequate access to housing. In Malaysia, one of the major social objectives in its development plan is the provision of affordable housing to all. Based on records available at Housing Development Corporation (HDC), the authority responsible for the development of affordable housing (low cost and low cost plus housing) in Sarawak showed that there was a big short in the supply of affordable housing in Sarawak, especially in Kuching and Samarahan Divisions. It is also observed that many of the aspired affordable housing buyers/ owners had to give up their ―dream homes‖ because of their inability to secure housing loan from the financial institutions or banks even though at HDC level, the house has already been offered to them. Records at HDC indicated that between 20-30% of the aspired affordable house owners had to reject the offer due to financial constraints. Therefore, based on the above mentioned issues, it is important to carefully study and analyse what are the factors that affect housing demand especially with regard to affordable housing in Kuching and Samarahan Divisions.